Modeling of trivalent chromium speciation in binding sites of marine macroalgae Sargassum Cymosum - F. B. de Souza (2013)
In this study, the marine macroalgae Sargassum cymosum was used for the purification of waters contaminated with trivalent chromium. FTIR analysis revealed a high heterogeneity of the biosorbent surface, as indicated by the different absorption peaks. Biomass titration revealed two main functional groups, carboxylic and hydroxyl. The pK(1,H) value and the number of carboxylic groups were estimated as 3.05 +/- A 0.01 and 1.90 +/- A 0.01 mmol g(-1), respectively. An equilibrium model considering the metal speciation in aqueous solution was able to predict the experimental data at different pH values. Adsorption of chromium increases significantly with an increase of the solution pH. Furthermore, the speciation of the binding sites as a function of the solution pH was predicted, showing that Cr(OH)(2+) has a higher affinity than Cr3+ to the binding sites. A mass transfer model considering an intraparticle diffusion resistance was able to predict the kinetic data, showing that Cr3+ diffuses faster that CrOH2+.